UMP reaps success at MTE 09 - UMP, PNC (Penerbit UMP, 2009)
It was quite a successful outing for UMP at the recent Malaysia Technology Expo 2009 (MTE 2009) where our researchers won a total haul of 12 medals comprising three golds, two silvers and seven bronze. In additions UMP picked up a "Best Booth" award in the Bare Space Category.